Pengukuran Ergonomi Metode REBA pada Bagian Palleting di PT XYZ - Destiana Putri; Zacky Akbar; Diah Andianingsari (IMTechno: Journal of Industrial Management and Technology, 2021)
The Palleting process at PT XYZ, which is based in the Asahan area, is heavy work that is still done manually. Improper posture and receiving repeated static loads over a long period of time can result in musculoskeletal injury. Ergonomic analysis using the REBA method is one method for evaluating the body posture and work attitude of workers as a whole. In this study, an analysis of the REBA method was carried out on workers in the Palleting section at PT XYZ to determine the amount of risks faced by workers and the improvements that could be proposed. The study was conducted referring to the REBA worksheet by Hignett and McAtamney. From the studies that have been done, it was found that workers have a high risk with a value of 9. Suggestions that can be made include lowering the level holder, optimizing the position of the torso and fulcrum, and educating workers on work attitudes.